1994
DOI: 10.1128/jb.176.4.953-958.1994
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of glucose transport in Saccharomyces cerevisiae is modulated during growth on glucose

Abstract: By using a modified technique to measure glucose uptake in Saccharomyces cerevisiae, potential uncertainties have been identified in previous determinations. These previous determinations had led to the proposal that S. cerevisiae contained a constitutive low-affinity glucose transporter and a glucose-repressible high-affinity transporter. We show that, upon transition from glucose-repressed to -derepressed conditions, the maximum rate of glucose transport is constant and only the affinity for glucose changes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(170 citation statements)
references
References 24 publications
(23 reference statements)
6
160
1
3
Order By: Relevance
“…The results presented here, and other observations, indicate that metabolic reactions after translocation affect the rate of glucose uptake. In some studies v max was the same for both high-and low-affinity transport systems, and for uptake of hexoses transported by different systems (Mark & Romano, 1971;Scarborough, 1970b;Walsh et al, 1994). In Neurospora crassa it was shown that the maximum uptake rate was similar to the capacity of disrupted mycelium to phosphorylate glucose (Scarborough, 1970a).…”
Section: High-affinity Glucose Uptakementioning
confidence: 91%
See 1 more Smart Citation
“…The results presented here, and other observations, indicate that metabolic reactions after translocation affect the rate of glucose uptake. In some studies v max was the same for both high-and low-affinity transport systems, and for uptake of hexoses transported by different systems (Mark & Romano, 1971;Scarborough, 1970b;Walsh et al, 1994). In Neurospora crassa it was shown that the maximum uptake rate was similar to the capacity of disrupted mycelium to phosphorylate glucose (Scarborough, 1970a).…”
Section: High-affinity Glucose Uptakementioning
confidence: 91%
“…K s values determined for growth in both batch and chemostat cultures depend on substrate uptake, metabolism and growth. Many investigations, however, have focused on separation of the characterization of the uptake process from interfering effects of growth and metabolism by determination of initial glucose uptake rates of starved or washed cells (MacCabe et al, 2003;Mark & Romano, 1971;Torres et al, 1996;vanKuyk et al, 2004;Walsh et al, 1994), isolated plasma membrane vesicles (Fuhrmann et al, 1989) or by description of uptake of non-metabolizable glucose analogues (Brown & Romano, 1969;Moore & Devadatham, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose uptake was assayed as described (Walsh et al, 1994) at five concentrations of D-U-( 14 C)-glucose [1, 2.5, 5, 10 and 25 mM (371,297,148,74 and 30 MBq/mol,respectively)]. The data were fit to the Michaelis-Menten equation using ENZFITTER software (Elsevier-Biosoft).…”
Section: Glucose Transport Assaymentioning
confidence: 99%
“…At high glucose concentrations yeast exhibits lowaffinity glucose transport, and at low glucose concentrations or in the absence of glucose (e.g. after the diauxic shift of a glucose-grown batch culture) the affinity displayed by yeast for glucose is high (Bisson and Fraenkel, 1984;Walsh et al, 1994). These differences in affinity presumably reflect the substrate affinities of the individual hexose transport proteins synthesized under these conditions (Reifenberger et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Zero trans-influx rates of sugars were determined in a 5 s assay, according to Walsh et al (1994), at 30 uC with the modification that growth medium was used instead of phosphate buffer. Cold glucose concentrations were verified by using a glucose oxidase assay: glucose oxidase (Roche Diagnostics), peroxidase and ABTS in 0.5 M Tris/HCl were mixed with standard or sample and incubated at 37 uC for 1 h under slow agitation after which the absorbance at 415 nm was measured using a SPECTRAmax PLUS384 Microplate Spectrophotometer (Molecular Devices).…”
Section: Methodsmentioning
confidence: 99%